PENYULUHAN TENTANG MANFAAT OLAHAN TANAMAN HERBAL UNTUK MENJAGA BERAT BADAN PADA SISWA SMAN 1 SUKATANI - Masita Sari Dewi; Dea Natalia; Dimas Alfi Ananda Ananda; Rosiana Putri; Nurvidian Khasanah; Alifa Lammima Adinda; Cindy Fauziah; Lifia Putri Zahrotul (APDFI (Asosiasi Pendidikan Diploma Farmasi Indonesia), 2026)
Obesity is a rapidly emerging nutritional problem worldwide and adolescents are no exception. Based on WHO studies, in 2015 about 2.3 billion adolescents aged 15 years and over were overweight and of these, more than 700 million were obese. Objective: This counseling activity aims to increase the understanding and awareness of SMA Negeri 1 Sukatani students regarding the importance of maintaining ideal body weight and being able to know and utilize herbal plants to reduce and maintain ideal body weight. Methods: Counseling is carried out by presenting material about the dangers of obesity and weight loss herbal plants and conducting demonstrations of making processed herbal weight loss plants. The activity was carried out for 120 minutes, consisting of 10 minutes of pretest, 60 minutes of material delivery and question and answer session, 40 minutes of demonstration and then ended with a 10-minute posttest. Results: Based on the evaluation results using the pretest method before carrying out the activity, the overall average value obtained by the students was 74.35% and based on the posttest results after carrying out the activity, the overall average value obtained by the students was 93.48%. This shows that counseling activities can increase the knowledge of participants very significantly. Conclusion: Participants' knowledge about the dangers of obesity and weight loss herbal plants increased after education on the use of herbal plants to maintain ideal body weight.